1986
DOI: 10.1002/jcp.1041260307
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional regulation of ornithine decarboxylase activity

Abstract: We have used a Chinese hamster ovary cell line (DF3) that overproduces ornithine decarboxylase (ODC) to examine various parameters in the cell cycle-dependent regulation of this enzyme. Under a variety of conditions, alterations in the activity of ODC were accompanied by parallel changes in the levels of the protein, as measured by immunologically cross-reactive material (CRM). While putrescine has been known to suppress the induction of ODC, we have found that in DF3 cells 10(-4)M ornithine completely suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
1

Year Published

1987
1987
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 30 publications
2
16
0
1
Order By: Relevance
“…Our findings are in agreement with an earlier study demonstrating an ATP requirement for the decay of ODC activity [45]. However, they contradict two recent studies which concluded that ODC degradation is an ATP-independent process [46, 471. It is unclear how we can reconcile our conclusions and those of one of the other studies [46], as in each case a similar experimental approach was utilized. In the study of Glass and Gerner [47], however, clear experimental support for such a conclusion was not provided.…”
Section: Discussionmentioning
confidence: 79%
“…Our findings are in agreement with an earlier study demonstrating an ATP requirement for the decay of ODC activity [45]. However, they contradict two recent studies which concluded that ODC degradation is an ATP-independent process [46, 471. It is unclear how we can reconcile our conclusions and those of one of the other studies [46], as in each case a similar experimental approach was utilized. In the study of Glass and Gerner [47], however, clear experimental support for such a conclusion was not provided.…”
Section: Discussionmentioning
confidence: 79%
“…Experimental manipulations of the levels of polyamines within cells result in rapid changes in ODC activity, but such treatments have no discernible effect on the amount of ODC mRNA (5,12,16,18,(27)(28)(29)35). It has been reported that the rate of synthesis of the enzyme, measured by metabolic labeling with radioactive amino acids, is reduced when intracellular polyamines are augmented, and the opposite result is found when cells are depleted of polyamines (11,12,16,20,21,25,27).…”
mentioning
confidence: 99%
“…translation (Dirks et al, 1986;Sertich & Pegg, 1987;Persson et al, 1986;Kahana & Nathans, 1985) and/or by post-translational mechanisms (Heller et al, 1976;McCann et al, 1979;Murakami & Hayashi, 1986). As a further test of this possibility, it would be interesting to determine whether 6-spermyne negatively regulates translation of AdoMetDC mRNA, but not ODC mRNA, in the reticulocyte-lysate translation system in vitro (Kameji & Pegg, 1987).…”
mentioning
confidence: 99%